A legitimacy‐based view of the impact of government venture capital on startup innovation: Evidence from a transition economy - Devarakonda, Ramakrishna; Liu, Aqi (Strategic Entrepreneurship Journal, 2024)
Abstract Research Summary This study examines the role of government venture capital (GVC) on startup innovation in a transition economy context. Drawing on institutional theory, we advance a contextual view of GVC by proposing that GVC positively impacts the innovation of startups in transition economies by serving as a sociocognitive legitimating endorsement. Furthermore, our study offers a contingent framework by showing that GVC endorsement will be more meaningful for startups deficient in organizational sources of legitimacy, such as political ties and social prestige. Regression analyses using a longitudinal data of Chinese venture‐backed biopharma and medical device startups founded during 2002–2017 offer broad support for our theory about the sociocognitive legitimating role of GVC in transition economy contexts. Managerial Summary We explore the role of government venture capital (GVC) in promoting startup innovation within transition economies. In such contexts, where startups often face skepticism and legitimacy issues, our research reveals that GVC can play a crucial role by providing socio‐cognitive legitimacy. Our study suggests that this “state backing” enables transition economy startups to gain the trust of external knowledge resource holders, enhancing their innovation prospects. Our findings emphasize the significance of GVC as a means of active government intervention for fostering startup innovation, especially for startups deficient in other avenues of legitimacy. This insight is valuable for entrepreneurs and policymakers in transition economy contexts.